Environmental Friendly conversion of locally available low-cost materials to zeolite - A.Smail, Heman; M.Shareef, Kafia; Ramli, Zainab (Sulaimani Journal for Pure and Applied Sciences, 2016)
Mordenite, NaY and NaX zeolites were hydrothermally synthesized from locally available low-cost materials such as, chert rock, barley husk, and shale clay without using organic templates, structure-directing agent, and additives. The as-synthesized zeolites were characterized by Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), X-ray Fluorescence (XRF) and Field Emission scanning electron microscopy (FESEM). The results verified that mordenite, NaY and NaX zeolites obtained from hydrothermal condition, present a good zeolitic properties and then can be suitable for using in adsorption, ion exchange and catalysis experiments. The properties of zeolite materials formed are strongly depended upon the composition and the type of raw materials used.
Keywords: ZeoliteBarley huskchert rockShale clay hydrothermal crystallization